MEASURING THE ABILITY IN DEBATE DEALING WITH FLUENCY AND ACCURACY OF THE THIRD SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT - Andi Muhammad Syukri; Dr. Hj. Mardiana (Universitas Islam Negeri Alauddin Makassar, 2016)
This study aimed to describe the ability of speaking skill in form of debating based on the fluency and accuracy rate capability. The study was designed in the form of qualitative descriptive study. The subjects in this research were six third semester students of English Education Department. The data were collected by using the methods of observation. Data were analyzed through fluency accuracy data, accuracy mesurement rubric and autenthic debate assessment rubric. The result indicated that (1) the ability of students’ at the third semester in conducting the debate still in the low level, as the fact that the frequency of stutters was significantly high and the tension attempted were quite visible and audible; (2) the outcome result of the rate of accuracy of the third semester students of English Education Depertment in conducting a debate was still low. The fact was gained by the actual fact in the field during the observation where pronunciation errors and basic grammar mistakes were still spotted in several places; (3) the debate ability of the third semester students of English Education was still low and need a further guide and developementBased on these findings, it can be concluded that the overall capability of students’ in conducting the debate was still unsatisfying. And as a suggestion that a three-stages structured debate forum club empowerment among students was highly recomended as a form of concern to enhance the intereset as well as the ability of the students to perform a public-speaking skill such as debating.